2023
DOI: 10.4102/hsag.v28i0.2234
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction among health professionals in a District of North West province, South Africa

Reabetswe A. Mere,
Thembi V. Simbeni,
Mmampedi Mathibe
et al.

Abstract: Background: Job satisfaction has become an area of relevance and debate in public health as it is directly linked to staff absenteeism, retention and turnover of the workforce and as such, influences the organisational commitment of the workers and the quality of health services provided. It is therefore essential to discern what drives healthcare professionals to remain working in the public health sector.Aim: This study aimed to determine job satisfaction and its associated factors among healthcare professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A Belgian study showed that a good work environment can effectively reduce job burnout and turnover intention of HCWs ( Bruyneel et al, 2023 ). A South African study showed that the work environment is a significant determinant of job satisfaction ( Mere et al, 2023 ). Overwork, poor management, and inappropriate work environment are the key factors responsible for job burnout ( Qi et al, 2022 , Zhao et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…A Belgian study showed that a good work environment can effectively reduce job burnout and turnover intention of HCWs ( Bruyneel et al, 2023 ). A South African study showed that the work environment is a significant determinant of job satisfaction ( Mere et al, 2023 ). Overwork, poor management, and inappropriate work environment are the key factors responsible for job burnout ( Qi et al, 2022 , Zhao et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%